Chemical composition of Mentha pulegium and Rosmarinus officinalis essential oils and their antileishmanial, antibacterial and antioxidant activities. (October 2017) - Bouyahya, Abdelhakim; Et-Touys, Abdeslam; Bakri, Youssef; Talbaui, Ahmed; Fellah, Hajiba; Abrini, Jamal; Dakka, Nadia
Abstract: The aim of the study was the determination of the chemical composition of Mentha pulegium L. and Rosmarinus officinalis L. essential oils and the evaluation of their antileishmanial, antibacterial and antioxidant activities. Essential oils (EOs) were isolated using steam distillation and the chemical composition was determined using GC-MS analysis. The antibacterial activity was tested against ten pathogenic strains using the diffusion method, the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) by microtitration assay. The antioxidant activity was estimated by DPPH free radical scavenging ability and ferric-reducing power. The antileishmanial activity was tested against Leishmania major, Leishmania tropica and Leishmania infantum using MTT (3-(4.5-dimethylthiazol-2yl)-2.5-diphenyltetrazolium bromide) assay. The yield of essential oils (v/w %) M. puleguim and R. officinalis based on dry weight were 5.4 and 2.7% respectively. GC/MS analysis of R. officinalis essential oil (ROEO) revealed the presence of 29 components, mainly represented by oxygenated monoterpenes (63.743%) and hydrocarbons monoterpenes (21.231%). Mentha pulegium essential oil (MPEO) revealed 21 components, mainly represented by oxygenated monoterpenes (83.865%). The major components of ROEO were α-pinene (14.076), 1, 8-Cineole (23.673) and camphor (18.743), while menthone (21.164) and pulegone (40.98) were the main major components of MPEO. M. pulegium and R. officinalis EOs showed a significant antioxidant activity compared with ascorbic acid and Trolox to the IC50 values of 58.27 ± 2.72 and 85.74 ± 7.57 μg/mL respectively revealed by reducing power assay. As for the antibacterial effect, the highest zone diameters were shown by the MPEO against Bacillus subtilis (30 ± 1.43 mm) and Proteus mirabilis (28 ± 1.32 mm). These values are significantly important compared with those of the commercialized antibiotic (Erythromycin and Chlorophenicol). The lowest MIC and MBC values were obtained with MPEO against S. aureus MBLA (MIC = MBC = 0.25% (v/v)). While, ROEO has exhibited a bactericidal effect against Listeria monocytogenes (MIC = MBC = 0.5% (v/v)), Bacillus subtilis (MIC = MBC = 1% (v/v)) and Escherichia coli (MIC = MBC = 1% (v/v)). For the antileishmanial effect, ROEO is the most active against L. major (IC50 = 1.2 ± 0.36 μg/mL. While, the MPEO has the most leishmanicidal effect against L. major (IC50 = 1.3 ± 0.45 μg/mL). These findings show that the EOs of M. pulegium and R. officinalis are good sources of bioactive molecules that could have potential applications in the food and pharmaceutical industries. Graphical abstract: Image 1 Highlights: Essential oils differentiate R. officinalis and M. pulegium. Antibacterial activity of both species results mainly from essential oils. Pepper mint indicate higher antibacterial and antioxidant activities than rosemary. Antileishmanial activity of both species showed interesting results.